PESTICIDAL EFFECT OF MENTHA SPICATA LEAVES EXTRACT ON TRIBOLIUM CONFUSUM (COLEOPTERA) - JAIN, JAYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
Effect of plant extract of Mentha spicata was studied on the development of Tribolium in infecting stored grain. Leaf extract of M. spicata was evaluated as stored rice grain protectant @ 2.5, 5.0 and 75 ml dose/ 50 g grain against the development of adults and larvae of confused flour beetle. The extract of test plants at 2.5, 5.0 and 7.5 ml dose in per 50.g grain prolonged the development on an average from 5 to 14 days. With increment in days and dose, mortality of beetles increases serial wise @ 2.5, 5.0 and 7.5 ml dose. Present study deals with the pesticidal effect of leaves of M. spicata on adults and larvae of Tribolium confusum.